2022
DOI: 10.3389/fpsyt.2021.771147
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatment-Induced State-Dependent Reconfiguration of Emotion Regulation Networks in Major Depressive Disorder

Abstract: Deficits in emotion regulation are the main clinical features, common risk factors, and treatment-related targets for major depressive disorder (MDD). The neural bases of emotion regulation are moving beyond specific functions and emphasizing instead the integrative functions of spatially distributed brain areas that work together as large-scale brain networks, but it is still unclear whether the dynamic interactions among these emotion networks would be the target of clinical intervention for MDD. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…They demonstrated that the predicted reduction rate of HAMD scores based on the strength of baseline dFC was significantly correlated with the actual reduction rate of HAMD scores. This finding also illustrated the role of ER networks in predicting the efficacy of antidepressants [ 46 ]. The above finding and our study suggest a direction in which future studies could focus, namely on the features with potential prediction efficacy found by previous studies, rather than screening features in the whole brain range by univariate statistics.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…They demonstrated that the predicted reduction rate of HAMD scores based on the strength of baseline dFC was significantly correlated with the actual reduction rate of HAMD scores. This finding also illustrated the role of ER networks in predicting the efficacy of antidepressants [ 46 ]. The above finding and our study suggest a direction in which future studies could focus, namely on the features with potential prediction efficacy found by previous studies, rather than screening features in the whole brain range by univariate statistics.…”
Section: Discussionmentioning
confidence: 57%
“…First, despite the high accuracy achieved in the current study, whether the model can still achieve high accuracy on a dataset with a larger sample size or from multiple sites remains to be verified. However, combined with previous studies, we have reason to believe that this large-scale brain network contains rich efficacy prediction information [ 46 ]. Second, the patients in this study used only escitalopram as antidepressants, which ensure the homogeneity of our sample, but in the real world, the patients used far more kinds of drugs, which makes it more difficult for the model to accurately predict.…”
Section: Discussionmentioning
confidence: 91%
“…In MDD, antidepressant therapy was significantly associated with DLPFC abnormalities (Nestor et al ., 2022 ; Zhukovsky et al ., 2021 ). As networks implicated in the cognitive regulation of emotion, the frontoparietal network and subcortical regions, including the bilateral fusiform gyrus, are related to the state-dependent reconstruction of emotion regulation networks in individuals with MDD due to antidepressant treatment (Zhao et al ., 2021 ). Males with MDD showed enhanced neural responses to acute psychosocial stress in the DLPFC and right frontoparietal network compared with females (Dong et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%